Physical Model Test of Artificial Freezing-Inclined Shaft - Jielong Sun; Xingzhou Chen; Mingming Qiu; Xueye Cao; Shaojie Chen (Advances in Civil Engineering)
Based on the vertical straight artificial freezing engineering in Northern Shaanxi, a three-dimensional (3D) physical simulation test system was developed, consisting of six parts, which are simulation box, shaft model, loading system, freezing system, external environment simulation system, and data acquisition system. The physical model and actual test results show that the 3D physical simulation test system is reasonable and reliable. The test model results show that the distance from the freezing pipe significantly affects the freezing wall temperature. For the case of four adjacent, two adjacent tangential freezing, and two adjacent axial freezing pipes, the cooling rates were 1.37, 2.79, and 1.96°C/h, respectively. The field measurement showed that the proximity to the freezing pipe increases the cooling rates. The cooling rates of points 1k#, 2k#, and 3k# were 25.61, 25.32, and 25.35 mm/d, respectively. The increment rates of vertical and horizontal freezing pressures with temperature were 8.78 and 2.97 kPa/°C, respectively. Furthermore, the freezing pressure time fitting formula was given. The calculated results of temperature and freezing pressure are consistent with the measured results, indicating the reasonability and reliability of the 3D physical simulation test scheme of the artificial freezing-inclined shaft in this work.